Desenvolvimento de um software para informatização do processo de enfermagem no hospital municipal de Castanhal/PA - SILVA, Marcelo da Silva e (2019)
The paper presented here proposes the development of software that will assist in the administration of the nursing processes of the medical clinic of the Municipal Emergency and Emergency Hospital of Castanhal. The management of hospitals and medical clinics has undergone important changes over the years and significant advances in the resources used to assist in the management of the most varied issues involving the hospital environment. This environment, considered complex, makes the hospitals are inserted in an increasingly competitive and demanding scenario. One of the solutions employed was the development of computational tools that managed the whole process of patient admission, control and that facilitated the generation of reports. In view of this, this work sought to reach the essential characteristics for software that can add the routine of the hospital environment. After the implementation of the software, it was identified great satisfaction of the subjects the usability of the software and the benefits that it would bring to their work routine. Given this, the work accomplished achieved its proposed objectives.